Combination Influence of Humic Acid and Chelated Iron on yield and quality of Broccoli (Brassica oleracea L) in Erbil, Iraqi Kurdistan Region. - Azad Ahmad Abdulla; Akram Othman Esmai; Haifa Sdiq yaseen (Zanco Journal of Pure and Applied Sciences, 2023)
This study was conducted during winter season of 2020, at Murtka farm, Qushtapa, Erbil with GPS reading of (latitude 36. 068 880 N, longitude 44. 031 990 E) and elevation 413. m.a.s.l. to study the role of 5 levels of humic acid( 0, 15 ,30,45 and 60 Mg ha-1 ), five levels of chelated iron (0, 4, 8, 12 and16 Mg ha-1) and their combinations o yield and quality of broccoli (Brassica oleracea L).The results indicated significant effect of humic acid and combination between humic acid and chelated iron on broccoli yield, the highest yield values of yield and 21.20 and 22.53 Mg ha-1 were recorded from application of 60Mg ha-1 humic acid and combination treatment of HA4-Fe3 or adding of 60 Mg ha-1 humic acid with 12 Mg ha-1 chelated iron respectively, while the lowest values 15.28 and 15.08 Mg ha-1 were obtained from HA0 and HA0-Fe0 respectively. The highest protein, potassium, phosphorus and Fe (30.25% ,4.10 g 100g-1 ,0.45 g 100 g-1 and 253 mg kg-1 head) were recorded from combination treatments of HA3-Fe2, HA4-Fe2, HA4-Fe2 and HA1-Fe4 respectively, while their lowest were obtained from control. The combination between humic acid and chelated iron (Fe-EDDHA) caused 1.71,2.37 ,1.60, 2.01 ,1.71 and1.49 times increase in nitrogen, phosphorus, potassium, iron protein content and broccoli yield respectively.